The Impact of Hyaluronic Acid Fillers on skin ageing: a clinical, histological and psychosocial analysis - Gąsiorek , Natalie; Gruchot, Hanna; Kuźnar, Anna; Bajorek, Julia; Bajorek, Michał (Journal of Education, Health and Sport, 2026)
Hyaluronic acid, a fundamental component of the extracellular matrix, plays an essential role in preserving skin elasticity, hydration, and structural cohesion. The clinical component of the analysis reviews the effectiveness of HA-based injectable formulations commonly used in aesthetic dermatology. The histological discussion focuses on tissue-level changes following HA administration, including stimulated collagen production, fibroblast activation, and remodelling of the extracellular environment. On the psychosocial level, the study evaluates how such procedures affect patients’ quality of life, self-image, emotional well-being, and overall self-worth. This study aims to comprehensively explore the influence of hyaluronic acid (HA) fillers on the multifaceted process of skin ageing, incorporating clinical, histological, and psychosocial perspectives.